2023
DOI: 10.1097/md.0000000000032693
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Fuzheng Yugan Mixture on COVID-19 based on network pharmacology and molecular docking

Abstract: After the World Health Organization declared coronavirus disease 2019 , as a global pandemic, global health workers have been facing an unprecedented and severe challenge. Currently, a mixturetion to inhibit the exacerbation of pulmonary inflammation caused by COVID-19, Fuzheng Yugan Mixture (FZYGM), has been approved for medical institution mixturetion notification. However, the mechanism of FZYGM remains poorly defined. This study aimed to elucidate the molecular and related physiological pathways of FZYGM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In recent years, network pharmacology has played an increasingly important role in the study of traditional Chinese medicine, and can effectively reveal the effects of Cuscuta sinensis on IBS-D. [17,18] In this research, the active constituents of C chinensis were retrieved from the TCSMP database as 11, which contained quercetin, kaempferol, isorhamnetin, and β-sitosterol. Quercetin has antiapoptotic, antioxidant, anti-inflammatory, antiviral, and anticancer effects on a variety of organ damage can play a certain protective effect, [19] can increase the tightness of intercellular junctions, improve the immune response of the intestinal tract, to maintain the relative balance of intestinal microecology, and to maintain the barrier function of the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, network pharmacology has played an increasingly important role in the study of traditional Chinese medicine, and can effectively reveal the effects of Cuscuta sinensis on IBS-D. [17,18] In this research, the active constituents of C chinensis were retrieved from the TCSMP database as 11, which contained quercetin, kaempferol, isorhamnetin, and β-sitosterol. Quercetin has antiapoptotic, antioxidant, anti-inflammatory, antiviral, and anticancer effects on a variety of organ damage can play a certain protective effect, [19] can increase the tightness of intercellular junctions, improve the immune response of the intestinal tract, to maintain the relative balance of intestinal microecology, and to maintain the barrier function of the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…AKT phosphorylation can induce insulin transport to the liver, pancreas, skeletal muscle, and adipose tissue to maintain glucose homeostasis, promote insulin secretion, and regulate the balance of lipid metabolism. [26,27] Research has demonstrated that diabetic rats exhibit insulin resistance and a decrease in PI3K expression, indicating the significant involvement of PI3K in insulin metabolism and blood-sugar regulation. [28] MAPK1 and IL-6 are related to inflammatory pathways, and are cytokines involved in the growth, differentiation, and functional regulation of various cells.…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology is a new field at the intersection of artificial intelligence and medicine, which is based on a large number of medical databases and computer algorithms to construct network relationship diagrams to illustrate the complex mechanisms of drug action. [ 21 , 22 ] The multi-target action in network pharmacology is consistent with the complex mechanism of action of diseases and herbal medicines, [ 23 ] which is free from the limitation of “one disease-one target-one drug” [ 24 ] and provides new ideas for the study of herbal formulations. [ 25 ] In order to extensively verify the pharmacological mechanism of GFW action on CSCC, we will adopt the analytical method of network pharmacology.…”
Section: Introductionmentioning
confidence: 99%